2018
DOI: 10.1002/tafs.10010
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and Reproductive Ecology of the Sicklefin Redhorse: An Imperiled Southern Appalachian Mountain Fish

Abstract: Many nongame fishes are poorly understood but are essential to maintaining healthy aquatic ecosystems globally. The undescribed Sicklefin Redhorse Moxostoma sp. is a rare, imperiled, nongame fish endemic to two southern Appalachian Mountain river basins. Little is known of its behavior and ecology, but this information is urgently needed for conservation planning. We assessed the spatial and temporal bounds of spawning migration, quantified seasonal weekly movement patterns, and characterized seasonal and spaw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 85 publications
(149 reference statements)
0
7
0
Order By: Relevance
“…First, our distribution of egg inputs based on the relative daily abundance of redhorses over the course of the migration might not reflect reality. Considering the sequential nature of redhorse migrations (Favrot, 2009; Kay et al., 1994), one might expect spawning activity to occur in pulses associated with the abiotic spawning preferences (i.e. temperature, discharge, photoperiod, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, our distribution of egg inputs based on the relative daily abundance of redhorses over the course of the migration might not reflect reality. Considering the sequential nature of redhorse migrations (Favrot, 2009; Kay et al., 1994), one might expect spawning activity to occur in pulses associated with the abiotic spawning preferences (i.e. temperature, discharge, photoperiod, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…shorter residence time = larger population size), which is challenging to estimate. Favrot (2009) found that the female residence time of sicklefin redhorse averaged 35 days in Hiwassee River tributaries—including several individuals in Brasstown Creek. However, this estimate appeared to be exaggerated by several females spending 80–300 days in their spawning streams.…”
Section: Discussionmentioning
confidence: 99%
“…Many riverine species rely on migrations between habitats and geographic areas where critical resources exist to complete components of their life cycle, such as reproduction and recruitment (Cooke et al 2011;Hicks et al 2020). Movement barriers cause declines in fish populations by impeding dispersal and reducing gene flow among populations (Gido et al 2016;Favrot and Kwak 2018). Where barrier removal is difficult or undesirable due to human infrastructure needs, bypass channels and active fish transportation above barriers are common methods to restore connectivity (Ovidio and Philippart 2002;Lusardi and Moyle 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Maturation occurs between 5 and 8 years (Jenkins, 1999;Jenkins, 2005). Adults live in rivers and large creeks year-round with migrations during spawning where females exhibit significant spawning site fidelity (Favrot, 2009;Favrot and Kwak, 2018). There is some evidence that males and females exhibit different movement patterns (Stowe, 2014).…”
Section: Introductionmentioning
confidence: 99%